MENGGUNAKAN MODEL PEMBELAJARAN DEBAT AKTIF UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN AGAMA KATOLIK DI SMPN 41 MEDAN - Nani Parangin Angin (Universitas Negeri Medan, 2022)
This study aims to increase students' learning motivation with an active debate learning model in the field of Catholic religious studies with the topic